2014
DOI: 10.1155/2014/170941
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Tobacco Use among School Going Adolescents in Delhi, India

Abstract: Background. Tobacco use is one of the major preventable causes of premature death and disease in the world. Many psychosocial factors were found to influence tobacco use. Therefore the present study was designed to determine the role of psychosocial factors associated with tobacco use among school going adolescents in Delhi, India. Methods. Cross-sectional study was conducted from February 2013 to September 2013 in four government schools in South district of Delhi, India. The questionnaire contains questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
8
33
0
Order By: Relevance
“…Using a large sample of adolescents from different European cities, the results confirm earlier findings on the strong relationship between personal income and smoking 1, 2, 3, 4, 5, 6, 7. Additionally, we found that personal income had an independent association with smoking, and did not act as a mere proxy of family SES.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using a large sample of adolescents from different European cities, the results confirm earlier findings on the strong relationship between personal income and smoking 1, 2, 3, 4, 5, 6, 7. Additionally, we found that personal income had an independent association with smoking, and did not act as a mere proxy of family SES.…”
Section: Discussionsupporting
confidence: 89%
“…This association was observed in middle‐income countries such as China 3 and India 1, 4, and high‐income countries and regions such as England 5, Scotland 8 and the United States 7. The relationship was also observed for various indicators such as current smoking 3, 4, 7, 8, heavy smoking 5 and amount spent on cigarettes 6.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This might be an indicator of the child's access to disposable income. Similar findings have been reported in China and India 29,30 it might be worthwhile to consider encouraging parents and guardians to limit the disposable income of their wards to help reduce access to cigarettes.…”
Section: Discussionsupporting
confidence: 73%
“…In many societies in Africa, the cultural norm of respect for elders is rife, and the possibility of punishment for those who disobey elders exists 30 . So when…”
Section: Discussionmentioning
confidence: 99%